Digital economy, green innovation and regional resource allocation efficiency: evidence from 257 cities in China - Jiang, Li; Zhang, Min; Hu, Shihui (Frontiers in Environmental Science, 2025)
IntroductionThe digital economy is reshaping economic structures and resource flows, but its role in enhancing resource allocation efficiency within the framework of green development has not yet been fully explored.MethodsThis paper analyzes panel data from 257 Chinese cities to investigate how the digital economy influences regional resource allocation efficiency, with a focus on the mediating role of green innovation.ResultsThe results show that the digital economy significantly improves resource allocation efficiency, with nonlinear effects characterized by increasing marginal returns. Mechanism tests reveal that the digital economy optimizes resource allocation by fostering green innovation. Heterogeneity analysis indicates that in eastern regions and areas with strong environmental regulations, the digital economy promotes both substantive and strategic green innovations, leading to higher efficiency. In mid-western regions, only substantive green innovation has a significant effect, while regions with weak environmental regulations experience less pronounced impacts.DiscussionThis study offers insights into leveraging green innovation to achieve efficient resource allocation and strengthen environmental resilience in the digital era.